2020
DOI: 10.1111/tmi.13450
|View full text |Cite
|
Sign up to set email alerts
|

Achieving a high cure rate with direct‐acting antivirals for chronic Hepatitis C virus infection in Cameroon: a multi‐clinic demonstration project

Abstract: Objectives Highly effective direct‐acting antivirals (DAAs) for Hepatitis C treatment are largely inaccessible in sub‐Saharan Africa. Data on treatment feasibility and outcomes in clinical settings are limited. We assessed the feasibility of achieving a high (≥90%) cure rate with DAAs in six gastroenterology clinics in Cameroon. Methods Patients with chronic Hepatitis C virus (HCV) infection were treated for 12 or 24 weeks with ledipasvir/sofosbuvir, ledipasvir/sofosbuvir/ribavirin or sofosbuvir/ribavirin, dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Wilder et al (2016) reported a similar SVR in black and non-black patients (95% vs 97%) with genotype 1 HCV infection. For HCV genotype 2, treatment with Sofosbuvir/Ledipasvir for 12 weeks was associated with elevated SVR rates in the study of Gane et al (2017) Hamadou et al, 2018;Coyer et al, 2020;Lawson-Ananissoh et al, 2019;Abozeid et al, 2018). A single-center study (Mairamou Hamadou et al, 2018) in Cameroon, 45/53 patients (84.9%) with HCV genotype 1 under Sofosbuvir/Ledipasvir  Ribavirin obtained an SVR, lower compared to our results.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Wilder et al (2016) reported a similar SVR in black and non-black patients (95% vs 97%) with genotype 1 HCV infection. For HCV genotype 2, treatment with Sofosbuvir/Ledipasvir for 12 weeks was associated with elevated SVR rates in the study of Gane et al (2017) Hamadou et al, 2018;Coyer et al, 2020;Lawson-Ananissoh et al, 2019;Abozeid et al, 2018). A single-center study (Mairamou Hamadou et al, 2018) in Cameroon, 45/53 patients (84.9%) with HCV genotype 1 under Sofosbuvir/Ledipasvir  Ribavirin obtained an SVR, lower compared to our results.…”
Section: Discussioncontrasting
confidence: 66%
“…A single-center study (Mairamou Hamadou et al, 2018) in Cameroon, 45/53 patients (84.9%) with HCV genotype 1 under Sofosbuvir/Ledipasvir  Ribavirin obtained an SVR, lower compared to our results. But a multicenter study in Cameroon (Coyer et al, 2020) J o u r n a l P r e -p r o o f Abozeid et al (2018), in Egypt had reported no difference in terms of efficacy between the Sofosbuvir/Ledipasvir  Ribavirin regimen (generics: 100% vs branded molecules: 98.2%; p=0.729) and Sofosbuvir/Daclatasvir  Ribavirin (generics: 97.8% vs. branded molecules: 98.1%; p=0.729).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prices of WHO-recommended DAAs for HCV vary substantially (US$200–45 000 for a curative course), but prices have been dropping, and most LMICs should be able to buy generic medicines at affordable prices[ 2 , 43 ]. Currently, HCV can be treated within 8–12 wk with highly effective DAAs and high cure rates[ 44 , 45 ]. Introducing locally produced pharmaceutical products paves the way for further lowering prices.…”
Section: Access To Medicine/preventive Measures For Hbv and Hcv In Re...mentioning
confidence: 99%
“…Another barrier for early treatment is the lack of screening programs to detect asymptomatic HCV patients. Having showed high cure rates for HCV carriers with DAAs in clinical settings in Cameroon (Coyer et al, 2020), accessibility and provision of the HCV care continuum should subsequently be addressed to ensure effective large-scale implementation and potential elimination.…”
Section: Introductionmentioning
confidence: 99%